Sobolev LVG analysis of aminomethanol and N-methylhyroxylamine:potential spectral lines for their detection in a cosmic object - Sharma, M. K.; Chandra, S. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Aminomethanol (NH2CH2OH) and N-Methylhydroxylamine (CH3NHOH) are isomers of each other, and have astrochemical importance. To our knowledge, they have not been analyzed so far in any terrestrial laboratory, and probably due to non-availability of accurate frequencies, they have not been searched in a cosmic object. It is well known that physical conditions in cosmic objects are very different as compared to those in our terrestrial laboratories. Therefore, these molecules may exist in the interstellar medium. For having information about the potential spectral lines of these molecules, we have obtained their rotational and centrifugal distortion constants, and electric dipole moment with the help of the GAUSSIAN software using B3LYP method, and augcc- pVDZ and aug-cc-pVTZ basis sets, separately. As the electric dipole moment has comparable components along all the three a, b and c axes, we have considered all the three types of radiative transitions together, and have calculated radiative transition probabilities for all the three kinds of radiative transitions. Considering a, b and c type transitions together, we have performed Sobolev LVG analysis of each molecule, where the collisional rate coefficients have been obtained using a scaling law. Considering energy levels up to 300 cm-1, we have found 181 weak MASER lines and 112 anomalous absorption transitions of NH2CH2OH, and 21 weak MASER lines and 28 anomalous absorption transitions of CH3NHOH, which may play important role for the identification of respective molecule in the ISM. Аминометанол (NH2CH2OH) и N-метилгидроксиламин (CH3NHOH) являются изомерами друг друга и имеют астрохимическое значение. Насколько нам известно, они до сих пор не анализировались ни в одной из земных лабораторий и, вероятно, из-за отсутствия точных частот их не искали в космических объектах. Хорошо известно, что физические условия в космических объектах сильно отличаются от условий в земных лабораториях. Следовательно, эти молекулы могут существовать в межзвездной среде. Для получения информации о потенциальных спектральных линиях этих молекул, мы получили их вращательные и центробежные константы дисторсии, а также электрический дипольный момент с помощью программы GAUSSIAN с использованием метода B3LYP и базисных наборов aug-cc-pVDZ, и aug-cc-pVTZ, отдельно. Поскольку электрический дипольный момент имеет сопоставимые компоненты по всем трем осям a, b и c, мы рассмотрели все три типа радиационных переходов вместе и рассчитали их вероятность радиационных переходов для всех трех типов. Рассматривая переходы типа a, b и c вместе, мы выполнили анализ LVG Соболева для каждой молекулы, где коэффициенты скорости столкновений были получены с использованием закона масштабирования. Рассматривая уровни энергии до 300 см-1, мы обнаружили 181 слабую линию MASER и 112 аномальных переходов поглощения NH2CH2OH, а также 21 слабую линию MASER и 28 переходов аномального поглощения CH3NHOH, которые могут играть важную роль для идентификации соответствующей молекулы в ISM.
Keywords: Chemical Physics